Triggering Cu-coordination change in Cu(ii)-Ala-His-His by external ligands. Issue 56 (24th June 2019) - Gonzalez, Paulina; Bossak-Ahmad, Karolina; Vileno, Bertrand; Wezynfeld, Nina E.; El Khoury, Youssef; Hellwig, Petra; Hureau, Christelle; Bal, Wojciech; Faller, Peter
Abstract : A switch in copper(ii )-coordination between the two motifs Xxx-Zzz-His (ATCUN) and Xxx-His in the hybride peptide Ala-His-His is induced by adding a ligand such as imidazole. Abstract : Copper(ii ) forms well-known and stable complexes with peptides having histidine at position 2 (Xxx-His) or 3 (Xxx-Zzz-His). Their properties differ considerably due to the histidine positioning. Here we report that in the hybrid motif Xxx-His-His, the Cu(ii )-complexes can be switched between the Xxx-His and the Xxx-Zzz-His coordination modes by addition of external ligands.